Development of information systems and clinical decision support systems for emergency departments: a long road ahead for Japan. Issue 11 (8th January 2013) - Inokuchi, Ryota; Sato, Hajime; Nakajima, Susumu; Shinohara, Kazuaki; Nakamura, Kensuke; Gunshin, Masataka; Hiruma, Takahiro; Ishii, Takeshi; Matsubara, Takehiro; Kitsuta, Yoichi; Yahagi, Naoki
Abstract : Emergency care services face common challenges worldwide, including the failure to identify emergency illnesses, deviations from standard treatments, deterioration in the quality of medical care, increased costs from unnecessary testing, and insufficient education and training of emergency personnel. These issues are currently being addressed by implementing emergency department information systems (EDIS) and clinical decision support systems (CDSS). Such systems have been shown to increase the efficiency and safety of emergency medical care. In Japan, however, their development is hindered by a shortage of emergency physicians and insufficient funding. In addition, language barriers make it difficult to introduce EDIS and CDSS in Japan that have been created for an English-speaking market. This perspective addresses the key events that motivated a campaign to prioritise these services in Japan and the need to customise EDIS and CDSS for its population.